Encephalopathy at admission predicts adverse outcomes in patients with SARS‐CoV‐2 infection. (16th June 2021) - Tang, Lei; Liu, Shixin; Xiao, Yanhe; Tran, Thi My Linh; Choi, Ji Whae; Wu, Jing; Halsey, Kasey; Huang, Raymond Y.; Boxerman, Jerrold; Patel, Sohil H; Kung, David; Liu, Renyu; et al.
Abstract: Aims: To determine if neurologic symptoms at admission can predict adverse outcomes in patients with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Methods: Electronic medical records of 1053 consecutively hospitalized patients with laboratory‐confirmed infection of SARS‐CoV‐2 from one large medical center in the USA were retrospectively analyzed. Univariable and multivariable Cox regression analyses were performed with the calculation of areas under the curve (AUC) and concordance index (C‐index). Patients were stratified into subgroups based on the presence of encephalopathy and its severity using survival statistics. In sensitivity analyses, patients with mild/moderate and severe encephalopathy (defined as coma) were separately considered. Results: Of 1053 patients (mean age 52.4 years, 48.0% men [ n  = 505]), 35.1% ( n  = 370) had neurologic manifestations at admission, including 10.3% ( n  = 108) with encephalopathy. Encephalopathy was an independent predictor for death (hazard ratio [HR] 2.617, 95% confidence interval [CI] 1.481–4.625) in multivariable Cox regression. The addition of encephalopathy to multivariable models comprising other predictors for adverse outcomes increased AUCs (mortality: 0.84–0.86, ventilation/ intensive care unit [ICU]: 0.76–0.78) and C‐index (mortality: 0.78 to 0.81, ventilation/ICU: 0.85–0.86). In sensitivity analyses, risk stratification survival curves for mortality and ventilation/ICU based on severe encephalopathy ( n  = 15) versus mild/moderate encephalopathy ( n  = 93) versus no encephalopathy ( n  = 945) at admission were discriminative ( p  < 0.001). Conclusions: Encephalopathy at admission predicts later progression to death in SARS‐CoV‐2 infection, which may have important implications for risk stratification in clinical practice. Abstract : Patients with severe acute respiratory syndrome coronavirus 2 infection have a high prevalence of neurologic manifestations, including headache, encephalopathy, dizziness, taste, and smell impairment. Patients with encephalopathy at admission predict later progression to death and mechanical ventilation/ICU admission in SARS‐CoV‐2 infection, which may have important implications for risk stratification in clinical practice.